A STUDY ON THE IMPACT OF OFF-THE-JOB EMBEDDEDNESS AND ON-THE-JOB EMBEDDEDNESS ON EMPLOYEE RETENTION IN MALAYSIAN PRIVATE UNIVERSITIES - Lim Yong Hooi; Mad Ithnin Salleh; Nor Azrin Md Latip, (INTERNATIONAL JOURNAL OF EDUCATION, PSYCHOLOGY AND COUNSELLING (IJEPC), 2024)
Employee retention (ER) among academic staff remains a major challenge for the universities and deserve more attention from researchers. Due to radical change in teaching method place additional pressure on the academic staff and lead to high turnover. Job embeddedness can be more significantly explain the variance in ER. However, little research done to examine the relationship between Off-the-job-embeddedness (JEoff) and on-the-job-embeddedness (JEon). Furthermore, due to the unclear conclusion for the impact of JEoff and JEon on ER based on past studies, this study aims to exam the relationship between JEoff and JEon as well as both impact on ER. The stratified sampling technique was used to draw 482 samples from population. The model was tested by applying The Partial Least Squares Structural Equation Modelling (PLS-SEM). JEoff and JEon were found to have direct significant impact on ER. But the effect size of JEoff on ER is smaller as compared with JEon. Moreover, JEoff could be related to JEon significantly with the largest level of effect-size. ER could be increased by enhancing JEoff through JEon as mediator. This study provides additional insight for human resource practitioners from Malaysian Private Universities in designing more effective system to retain their academic staff.